Sarraounia, une reine africaine entre histoire et mythe littéraire (Niger, 1899-2010) - Elara Bertho (Genre & Histoire)
The writer Abdoulaye Mamani, using oral myths from the area of Lougou, Niger, re-wrote the story of Queen Sarraounia, who was said to have fought the French Voulet-Chanoine column in 1899. Published in 1980, he intended his novel Sarraounia  to be a form of  historical authentification, despite the fact the figure of a warrior queen was little known, if not completely unknown, to historians. He thus contributed to the creation of a 'national myth', although the subversive dimension present in the original work were gradually eliminated. The article analyzes the processes at work in the construction of the memory of colonization, drawing on the study of oral narratives from Lougou, Mamani’s novel and later re-writings of the myth.